Early Myocardial Strain Reduction and miR-122-5p Elevation Associated with Interstitial Fibrosis in Anthracycline-Induced Cardiotoxicity - María de Regla Caballero-Valderrama; Elisa Bevilacqua; Miriam Echevarría; Francisco Javier Salvador-Bofill; Antonio Ordóñez; José Eduardo López-Haldón; Tarik Smani; Eva M. Calderón-Sánchez (Biomedicines, 2024)
Echocardiographic myocardial strain is crucial for early detection of anthracycline-induced cardiotoxicity, particularly in patients at moderate or high risk. Background/Objectives: This study investigates changes in global longitudinal strain (GLS) in breast cancer patients with low baseline risk for cardiotoxicity during cancer therapy. We also examined the relationship between echocardiographic strain, structural myocardial changes, and microRNA (miRNA) dysregulation associated with cancer treatment using an animal model. Methods: Echocardiography and blood tests were examined in 33 breast cancer patients with low baseline risk for cardiotoxicity during anthracycline treatment, with a follow-up at 12 months. Additionally, 16 Wistar rats received epirubicin (20 mg/kg over 4 weeks) to examine cardiac strain and structural changes. Moreover, circulating miRNA levels were assessed in patients’ serum using microarray at the end of the treatment and further analyzed in peripheral blood from the animal model. Results: Pathological GLS values were observed in 27.27% of patients after four cycles, with 15.15% showing reduced left ventricular ejection fraction (LVEF) after 12 months. In the animal model, epirubicin-induced circumferential strain (CS) decrease correlates with myocardial fibrosis assessed histologically and by a significant increase in COL1 and TGFB2 expression. Furthermore, we found a significant decrease in aquaporin1 expression associated with the presence of vacuoles in treated rats. Furthermore, dysregulation in the expression of miRNAs was observed in patients with cardiotoxicity. Among them, hsa-miR-122-5p is increased in both patient and rat serum post-treatment. Conclusions: A notable percentage of low-risk patients exhibited cardiac strain reduction due to cardiotoxicity. Epirubicin treatment caused structural heart changes in rats, highlighting miR-122-5p as a potential fibrosis marker that correlated with echocardiographic parameters.